Australian childhood immunisation coverage, 1 July to 30 September cohort, assessed as at 31 December 2013 - Hull, Brynley P; National Centre for Immunisation Research and Surveillance (Communicable Diseases Intelligence, 2014)
The National Centre for Immunisation Research and Surveillance of Vaccine Preventable Diseases (NCIRS) provides commentary on the trends in the Australian Childhood Immunistaion Register data for children vaccinated at 12, 24 and 60 months of age.